Efficacy and safety analysis of massage and medium-frequency electrotherapy in the treatment of congenital muscular torticollis in infants - Lin, Kai-nan; Sun, Ai-jing; Wang, Xiang-xuan (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the efficacy and safety of massage combined with medium-frequency electrotherapy (M&MFE) in the treatment of congenital muscular torticollis (CMT) in infants.MethodsWe retrospectively analyzed the clinical data of 48 CMT patients who underwent M&MFE treatment at the Fujian Children's Hospital and Traditional Chinese Medicine Department of Ao-feng Community Health Service Center in Tai-jiang District, Fuzhou City, from May 2021 to December 2023. All patients had complete follow-up data, received continuous treatment for 6 months, and were followed up for at least 1 year. The following parameters were evaluated: cervical range of motion (ROM) and muscle function scale to assess efficacy, and complications during treatment were recorded.ResultsA total of 48 patients were included, comprising 26 females and 22 males. The age at initial treatment ranged from 21 to 135 days, with a mean of (41.2 ± 25.4) days. There were 21 cases with left-side involvement and 27 cases with right-side involvement. All patients were followed up for 13–20 months, with a mean follow-up duration of (14.5 ± 2.6) months. By the end of follow-up, 5 patients (10.4%) underwent surgical release. The overall efficacy rate was 89.6%, and significant improvements were observed in cervical ROM and muscle function scores after treatment (P < 0.05). No complications related to the skin, blood vessels, nerves, or muscles occurred during the treatment period.ConclusionThe combination of manual massage and local medium-frequency electrotherapy is a safe and effective non-surgical treatment option for treating infants with congenital muscular torticollis. It significantly improves the neck range of motion and function, and has high clinical promotion value.